(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
The present study represents an attempt to improve wet wear resistance through electroplating coating samples of low carbon steel. Minitab 18 program was used to precipitate a composite coating layer (Ni-SiC) because it is used in many industrial applications that require wear resistance. The samples were coated using different variables as inputs: SiC concentration, stirring velocity (r.p.m) and deposition time (min) for three levels using central composite design for design laboratory experiments. The factors of coating thickness (C.T), surface roughness (Ra) and Brinell hardness (HB) were adopted as outputs response and a complete analysis of variances (ANOVA) at constants significances levels of %5, was done to fully identify the most significant parameters. The surface response methodology (RSM) was used to give an optimal model with the best optimum properties such as Brinell hardness, surface roughness and coating thickness to improve wet wear resistance of low carbon steel samples. The results showed respectively that the SiC wt.% was the most effective on all the outputs response then deposition time (min) and stirring velocity (r.p.m).